The Social and Political Implications of Bureaucratization - Mises, Ludwig von (2014)
This text addresses some wider implications of the expansion of the public sector and bureaucratic management that accompanies it, such as the conflict between the interests of employees and citizens, the influence of bureaucracy in the academic activity and the contradictions between goals of different areas of public administration. It is of particular interest the use of the hypothesis of self-interested public servants in the analysis, which anticipates the public choice tradition.